Indonesian and Australian Employee Responses to Interactional Injustice: The Roles of Negative Affect and Power Distance - Lydia Rahardjo; Julie Fitness (Faculty of Psychology, Universitas Surabaya, 2013)
The aims of this study were to explore employees’ emotional and behavioral responses to perceived injustice at work, and to determine the extent to which their responses depended on the power distance (PD) between employees and supervisors at the individual, organizational, and national levels. Data were collected using an anonymous online survey of 81 Australians (a low PD society) and 107 Indonesians (a high PD society). The results showed that perceptions of interactional injustice: (a) were negatively related to constructive behavior, (b) were positively related to the destructive behaviors of exit and neglect through negative affect mediation, (c) interacted with PD in influencing exit behavior, such that participants who perceived high national and organizational PD were less likely to quit the organization even if they experienced a high level of negative affect in response to perceived interactional injustice. Together, the results highlighted the importance of negative affect and power distance perceptions in predicting employees’ responses to perceived interactional injustice, especially quitting behavior. The results also suggest that cultural values should be taken into account when addressing problems related to organizational justice and supervisor-subordinate relationships. Tujuan penelitian ini adalah untuk mengeksplorasi respons emosi dan perilaku karyawan terhadap ketidakadilan di tempat kerja, dan untuk meneliti sejauh mana respons mereka dipengaruhi oleh power distance (PD) antara karyawan dan atasannya pada tingkat individual, organisasional, dan nasional. Data dikumpulkan menggunakan survei online anonim terhadap 81 warga Australia (masyarakat dengan tingkat PD rendah) dan 107 warga Indonesia (masyarakat dengan tingkat PD tinggi). Hasil penelitian menunjukkan bahwa persepsi karyawan mengenai ketidakadilan interaksional: (a) berkorelasi negatif dengan perilaku konstruktif, (b) berkorelasi positif dengan perilaku destruktif, yaitu ”keluar dari pekerjaan” dan ”melalaikan pekerjaan,” melalui efek mediasi dari afeksi negatif, (c) berinteraksi dengan PD dalam memengaruhi perilaku ”keluar dari pekerjaan”, yaitu partisipan dengan tingkat PD tinggi pada level nasional dan organisasional cenderung untuk tinggal di organisasi tersebut meskipun mereka merasakan emosi negatif sebagai akibat dari ketidakadilan interaksional yang dialami. Secara keseluruhan, hasil penelitian ini menggarisbawahi pentingnya afeksi negatif dan persepsi mengenai power distance dalam memprediksi respons-respons karyawan terhadap ketidakadilan interaksional, terutama perilaku ”keluar dari pekerjaan.” Penelitian ini juga menunjukkan bahwa nilai-nilai budaya sepatutnya dipertimbangkan dalam menangani masalah yang berkaitan dengan keadilan organisasional dan hubungan bawahan-atasan.